Antioxidant activity of Micractinium sp. (Chlorophyta) extracts against H2O2 induced oxidative stress in human breast adenocarcinoma cells - Onur Bulut; Işkın Engin Köse; Çağla Sönmez; Hüseyin Avni Öktem (Scientific Reports)
Abstract In response to the growing demand for high-value bioactive compounds, microalgae cultivation has gained a significant acceleration in recent years. Among these compounds, antioxidants have emerged as essential constituents in the food, pharmaceutical, and cosmetics industries. This study focuses on Micractinium sp. ME05, a green microalgal strain previously isolated from hot springs flora in our laboratory. Micractinium sp. cells were extracted using six different solvents, and their antioxidant capacity, as well as total phenolic, flavonoid, and carotenoid contents were evaluated. The methanolic extracts demonstrated the highest antioxidant capacity, measuring 7.72 and 93.80 µmol trolox equivalents g−1 dry weight (DW) according to the DPPH and FRAP assays, respectively. To further characterize the biochemical profile, reverse phase high-performance chromatography (RP-HPLC) was employed to quantify twelve different phenolics, including rutin, gallic acid, benzoic acid, cinnamic acid, and β-carotene, in the microalgal extracts. Notably, the acetone extracts of Micractinium sp. grown mixotrophically contained a high amount of gallic acid (469.21 ± 159.74 µg g−1 DW), while 4-hydroxy benzoic acid (403.93 ± 20.98 µg g−1 DW) was the main phenolic compound in the methanolic extracts under heterotrophic cultivation. Moreover, extracts from Micractinium sp. exhibited remarkable cytoprotective activity by effectively inhibiting hydrogen peroxide-induced oxidative stress and cell death in human breast adenocarcinoma (MCF-7) cells. In conclusion, with its diverse biochemical composition and adaptability to different growth regimens, Micractinium sp. emerges as a robust candidate for mass cultivation in nutraceutical and food applications.